2012
DOI: 10.1371/journal.pone.0045939
|View full text |Cite
|
Sign up to set email alerts
|

Soil-Transmitted Helminth Infections and Correlated Risk Factors in Preschool and School-Aged Children in Rural Southwest China

Abstract: We conducted a survey of 1707 children in 141 impoverished rural areas of Guizhou and Sichuan Provinces in Southwest China. Kato-Katz smear testing of stool samples elucidated the prevalence of ascariasis, trichuriasis and hookworm infections in pre-school and school aged children. Demographic, hygiene, household and anthropometric data were collected to better understand risks for infection in this population. 21.2 percent of pre-school children and 22.9 percent of school aged children were infected with at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
67
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 15 publications
(18 reference statements)
16
67
7
Order By: Relevance
“…The pattern of rapid reinfection after antihelminthic treatment (in our case, we tested the follow-up fecal samples 6 months after treatment) has been consistently identified in geographically diverse populations in both children and adults, 46 and was previously confirmed in our study area. 8,25 In our scenario, we surmise that children in the intervention group were cleared of STH infection after each of the two rounds of antihelminthic treatment, but experienced high rates of reinfection within the subsequent months leading up to postintervention evaluation. In a 2012 article by Jia and others, helminth reinfections occur rapidly after treatment, particularly for A. lumbricoides and T. trichiura.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pattern of rapid reinfection after antihelminthic treatment (in our case, we tested the follow-up fecal samples 6 months after treatment) has been consistently identified in geographically diverse populations in both children and adults, 46 and was previously confirmed in our study area. 8,25 In our scenario, we surmise that children in the intervention group were cleared of STH infection after each of the two rounds of antihelminthic treatment, but experienced high rates of reinfection within the subsequent months leading up to postintervention evaluation. In a 2012 article by Jia and others, helminth reinfections occur rapidly after treatment, particularly for A. lumbricoides and T. trichiura.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analyses of binary outcome measures-STH prevalence, anemia prevalence, and school attendance-were performed using STATA's logistic regression model, also taking into account paired fixed effects and clustering at the township level. Following previous studies, 8,25,43 we adjusted for the following two sets of additional covariates at baseline survey in the multivariate analyses to increase statistical precision: student individual characteristics (gender; age; boarding status; belonging to the Dong, Miao, or Shui minority groups) and household characteristics (number of siblings, number of durable assets, parental migration status, educational attainment of parents). We also included pair fixed effects at the township level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Published studies have documented that obtaining only a single fecal sample for A. lumbricoides and T. trichiuria can lead to underestimation of infection rates by up to 50%. 54,74 Sensitivity for low infection rates increased from 20 to 54% when three fecal samples were examined on separate days. 74,75 Although confounding factors were addressed in many of the primary studies identified for the current analysis, it is likely that there still may be unmeasured confounding factors which might have induced bias to this meta-analysis.…”
Section: Study Limitationsmentioning
confidence: 99%
“…54,74 Sensitivity for low infection rates increased from 20 to 54% when three fecal samples were examined on separate days. 74,75 Although confounding factors were addressed in many of the primary studies identified for the current analysis, it is likely that there still may be unmeasured confounding factors which might have induced bias to this meta-analysis. There could have been a temporal mismatch between the data, which came from several different time points, ranging from 2003 to 2013.…”
Section: Study Limitationsmentioning
confidence: 99%